2017
DOI: 10.1002/jsfa.8760
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion complexes of yellow bell pepper pigments with β‐cyclodextrin: preparation, characterisation and application as food natural colorant

Abstract: The complex obtained by inclusion method B promoted better colour protection for the beverage compared with the use of the crude extract, showing that the molecular inclusion of yellow bell pepper carotenoids can provide good results for that purpose. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Furthermore, Šeregelj et al [ 20 ] showed that the fortification of yogurt with natural colorants (from bell pepper wastes) improved its sensory attributes and positively affected the viability of lactic acid bacteria in yogurt during storage. Additionally, Lobo et al [ 90 ] demonstrated that extracts from yellow bell peppers could be used as a natural pigment in isotonic drinks. In general, adding bioactive compounds from bell pepper wastes to foods as a functional ingredient is a technological and viable alternative to the valorization of food wastes [ 91 ].…”
Section: Biological Activities Of Bell Pepper Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Šeregelj et al [ 20 ] showed that the fortification of yogurt with natural colorants (from bell pepper wastes) improved its sensory attributes and positively affected the viability of lactic acid bacteria in yogurt during storage. Additionally, Lobo et al [ 90 ] demonstrated that extracts from yellow bell peppers could be used as a natural pigment in isotonic drinks. In general, adding bioactive compounds from bell pepper wastes to foods as a functional ingredient is a technological and viable alternative to the valorization of food wastes [ 91 ].…”
Section: Biological Activities Of Bell Pepper Extractsmentioning
confidence: 99%
“…On the other hand, bioactive compounds extracted from red bell peppers have been used as natural colorants of yogurt and isotonic drinks [20,89,90]. Mendes-Gomes et al [89] added encapsulated bioactive compounds extracted from bell peppers to improve the color, sensory attributes, and nutritional value of yogurt.…”
Section: Applications Of Bioactive Compounds From Bell Peppers In Food Industrymentioning
confidence: 99%
“…Nevertheless, some positive results have been obtained during the last years. In particular, a recent study of carotenoids/CD complexes shows that molecular inclusion of yellow bell pepper carotenoids (lutein, zeaxanthin, α-cryptoxanthin, α-carotene and β-carotene) into the CD cavity provides good results for color protection for beverages compared with the use of the crude extract [30]. The authors have measured the color stability during storage under irradiance and in the absence of light at temperatures between 25 and 31 °C for 21 days and demonstrated higher stability of the color indexes in isotonic drinks colored with the inclusion complexes compared to colored with crude yellow bell pepper extract.…”
Section: Inclusion Complexesmentioning
confidence: 99%
“…Most of the published evidence on the use of inclusion complexes as encapsulation systems relies on a model or proof-of-concept guest compounds, and the complex forma-tion methodologies have been tested at laboratory or bench scale. Several authors have employed encapsulation with β-cyclodextrin since it is a molecule of great commercial interest, cheaper compared to its α and γ counterparts, and allows the encapsulation of hydrophobic molecules as it has a non-polar center due to the arrangement of the internal hydrogens of the truncated cone, while increasing the hydrophilicity of these molecules due to the conformation of the external hydrogens [9,10]. Another benefit of using this molecule in the food industry is its toxicity as it is considered a GRAS (generally recognized as safe) molecule by the FDA [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another benefit of using this molecule in the food industry is its toxicity as it is considered a GRAS (generally recognized as safe) molecule by the FDA [11]. The use of these encapsulations in natural extracts has been of great interest in the food industry, since they generate great thermal, chemical and color stability in the product and permit exploring the use of natural ingredients as colorants to replace the controversial use of artificial colorants [9,12,13]. In order to enhance the commercial application of this encapsulation strategy for natural carotenoids in the food industry, attempts must be made to propose possible scaleups based on the published evidence on encapsulation of carotenoids, or carotenoid-rich extracts, via the formation of cyclodextrin inclusion complexes.…”
Section: Introductionmentioning
confidence: 99%